Allan Octavian Hume (1829–1912): his development as an ornithologist until his departure from Etawah district, India, in 1867. Issue 2 (September 2022) - Prŷs-Jones, Robert P.
Abstract : The ornithological studies of Allan Octavian Hume (1829–1912), and the enormous bird collection he amassed, have been of exceptional importance to the development of knowledge of the south Asian avifauna. However, the paucity of his surviving personal correspondence and private papers has made it difficult to trace the development of his own ornithological interest. Nine field diaries of Hume's are held by the Natural History Museum, London. This paper draws on the first three of these, each covering periods of from one to a few months between late 1859 and late 1866, in combination with information from Hume's bird collection, also now largely held by the Natural History Museum. Together they shed light on the evolution of his ornithological knowledge and interest during his career in India up to the time of his departure from Etawah district, North-Western Provinces, where he had been Officiating Magistrate and Collector for eleven years from early 1856 to early 1867.